Capacitance-voltage fitting algorithm for doping profile characterisation of Mesa Diodes using MATLAB - Che Omar, Nuurul Iffah; Alang Md Rashid, Nahrul Khair; Hasbullah, Nurul Fadzlin (INSI Publications, 2012)
In this study, a capacitance-voltage fitting algorithm was developed using four region approximations and fitted against three GaAs mesa diodes. Doping and electric field profile measured and fitted are presented using MATLAB based programming. Results of 4-regions approach gave a better fitting in all the diodes compared to 3-regions approximation. It also showed good approximation to the mesa diodes measured C-V by using higher number of approximated region.